INTEGRATION OF PESANTREN AND MOSQUE FUNCTION IN TEACHING ISLAM IN SOUTH SULAWESI AND THEIR SIGNIFICANCE TOWARDS CONSISTENCY OF RELIGIOUS MODERATION - Iin Parninsih; Fatimah HS (Kawalu: Journal of Local Culture, 2022)
This article discusses the teaching of Islam through the integration of pesantren and mosques functions, focusing on South Sulawesi. This study is directed to see the significance of teaching in pesantren and mosques in producing and supporting consistency of religious moderation in Indonesia. This study uses a descriptive-analytical method, by applying the theory of cultural reproduction of Pierre Bourdieu, which includes arena and habitus as the main components, of which there is capital. From this, this study concludes that Islamic teaching in pesantren and mosques carried out by ulema has a strong significance in carrying out consistency of religious moderation in South Sulawesi, even in the Indonesian context. The social capital of the ulema in pesantren and mosques builds a social structure that places the ulema as local leaders (agents) in forming a moderate religious model. The significance of teaching Islam further becomes a great opportunity in maintaining and developing religious moderation in Indonesia which is carried out together with the government. The collaboration between the government and the ulema indicates the need for agreement in understanding the urgency of religious moderation in Indonesia. In the agreement, the government as the provider of facilities and infrastructure supports the Islamic teaching movement by the ulema. This is as happened in the process of teaching Islam at the beginning of Islamization in Indonesia, including in South Sulawesi.